Implementasi Analisis SWOT Strategi Pemasaran Produk BSI Griya di Bank Syariah Indonesia KCP Jepara - Husein, Nirmala Amelia; Ansori, Miswan (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
This research analyzes the marketing strategy for BSI Griya products at Bank Syariah Indonesia KCP Jepara using SWOT analysis. The results show that the product's main strengths are its usury-free sharia financing system and excellent service, while its weaknesses lie in the lack of promotion and strict financing procedures. Opportunities that can be exploited include high demand for housing and trends in sharia products, while the main threats come from competition with other banks and fluctuating economic conditions. It is hoped that implementing the right strategy can increase BSI Griya's market share and meet the needs of the Jepara community for sharia-based home ownership financing products.